The Concept of Stable Strategic Time Periods in Strategic Group Research - Fiegenbaum, A. (Institutional Knowledge at Singapore Management University, 1987)
This paper briefly reviews previous research on strategic groups and concludes that the concept needs further refinement. In particular, strategic grouping studies have typically ignored the influence of time on competitive strategy and have assumed homogeneity in strategic behavior over the time period researched. Therefore, a general analytical method is proposed in order to identify time periods of similarity in strategic behavior—so-called stable strategic time periods. It is argued that following the identification of stable strategic time periods meaningful strategic groupings of companies within industries can be derived and further analysis of the dynamics of strategic group shifts can be performed.